1991
DOI: 10.1073/pnas.88.23.10540
|View full text |Cite
|
Sign up to set email alerts
|

Excess brain protein oxidation and enzyme dysfunction in normal aging and in Alzheimer disease.

Abstract: The relationship between Alzheimer disease (AD) and aging is not currently known. In this study, postmortem frontal-and occipital-pole brain samples were obtained from 16 subjects with AD, 8 age-matched controls, and 5 young controls. These samples were analyzed both for protein oxidation products (carbonyl) and the activities of two enzymes vulnerable to mixed-function oxidation, glutamine synthetase and creatine kinase. Glutamine synthetase is more sensitive to mixed-function oxidation than creatine kinase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
653
4
10

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,175 publications
(692 citation statements)
references
References 29 publications
25
653
4
10
Order By: Relevance
“…Although there is controversy whether inflammation is causative or a consequence of the disease process, it is now clear that it can greatly influence its pathogenesis (Floyd 1999;Teunissen et al 2003). Even though aging and neurodegeneration share the same basic mechanisms, it is difficult to establish the limits between these two processes; there are mounting evidences that neurodegeneration might be an extension of the normal aging process, which might increase the susceptibility for neurotoxic events (Smith et al 1991;Swerdlow 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is controversy whether inflammation is causative or a consequence of the disease process, it is now clear that it can greatly influence its pathogenesis (Floyd 1999;Teunissen et al 2003). Even though aging and neurodegeneration share the same basic mechanisms, it is difficult to establish the limits between these two processes; there are mounting evidences that neurodegeneration might be an extension of the normal aging process, which might increase the susceptibility for neurotoxic events (Smith et al 1991;Swerdlow 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These reactive species can cause oxidative damage to proteins, lipids, and nucleic acids, leading for example to lipid peroxidation and DNA mutations (Mamelak 2007;Valko et al 2007). It is believed that those changes can be more intense in neurodegenerative disorders, including Alzheimer's disease (AD), Parkinson's disease, and amyotrophic lateral sclerosis which have an age-related great incidence (Floyd 1999;Smith et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…27 However, patients with AD have been reported to have significantly lower brain glutamine synthetase (GS) activities than age-matched controls. 33 In parallel, ammonia formation may be increased in the brain in AD following hydrolysis of proteins or deamination of aminopurines and aminopyrimidines. 33 Collectively, present data and that of other studies may implicate an impairment of brain ammonia metabolism in AD.…”
Section: Discussionmentioning
confidence: 99%
“…33 In parallel, ammonia formation may be increased in the brain in AD following hydrolysis of proteins or deamination of aminopurines and aminopyrimidines. 33 Collectively, present data and that of other studies may implicate an impairment of brain ammonia metabolism in AD. Moreover, in this context it has been reported that ammonia levels are increased in blood and brain of patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…The other specific markers of protein oxidation are O-tyrosine (a marker for hydroxyl radical) and 3-nitrotyrosine (a marker for RNS). An increase in the levels of protein carbonyls is observed in a number of pathological conditions such as, Alzheimer's disease [96], parkinson's disease [97], muscular dystrophy [98], cataractogenesis [99], Rheumatoid Arthritis [100], diabetes [101], progeria, atherosclerosis, respiratory dystrous syndrome, Werner's syndrome [91], and ageing [96,102].…”
Section: Proteinsmentioning
confidence: 99%